The Effect of Interactive Engagement Strategy Using Quizizz on Students' Critical Thinking Skills on Chemical Bonding Material - Pratiwi, Yezsica; M.Noer, Asmadi; Anwar S, Lenny (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper discusses the effect of an interactive engagement strategy using Quizizz on students' critical thinking skills on chemical bonding material. This research used a quasi-experimental design because not all factors influencing learning can be controlled. This research was conducted in two experimental classes, the experimental and the control classes. The experimental class was given treatment in the form of an interactive engagement strategy using Quizlet. And the control class was given conventional model treatment. The sampling technique in this research is purposive sampling, which considers the homogeneity of the sample (class). The experimental and control class samples were 29 students from class X at MAN 1 Pekanbaru. The research results show that the ability to infer, namely making conclusions and presenting problems, dominates with the highest percentage value of 85%. On the other hand, analytical skills, which involve finding causes, assessing impacts, and predicting further impacts, recorded the lowest percentage with 50%. Overall, the average percentages for the four indicators reached 67.5%, which is in the good category. The Independent Sample T-Test statistical test, with a significance value (sig) of 0.000, revealed a significant difference in scientific literacy abilities between experimental and control class students. Of the N-Gain analysis, it is known that the average gain score for critical thinking skills in the experimental class (0.50 or 50%) is in the medium category, while the control class only reached 0.30 (30%), which is included in the low category. This shows a more significant increase in learning outcomes for critical thinking skills in the experimental class compared to the control class.